Fatty Acid Metabolism-Related lncRNAs are Potential Biomarkers for Predicting Prognoses and Immune Responses in Patients with Skin Cutaneous Melanoma - Wang X; Yang X; Zhang Y; Guo A; Luo S; Xiao M; Xue L; Zhang G; Wang H (Dove Medical Press, 2023)
Xing Wang,1,2,* Xiaojing Yang,1,3,* Yiming Zhang,1 Afei Guo,1 Suju Luo,1 Meng Xiao,1 Lu Xue,1 Guohui Zhang,2 Huiping Wang1 1Department of Dermatovenereology, Tianjin Medical University General Hospital, Tianjin, People's Republic of China; 2Department of Dermatovenereology, Baotou Central Hospital, Baotou City, Inner Mongolia, People's Republic of China; 3Department of Dermatovenereology, the First Affiliated Hospital of Hebei North University, Zhangjiakou, Hebei, People's Republic of China*These authors contributed equally to this workCorrespondence: Huiping Wang; Guohui Zhang, Email huiping1208@163.com; 1259314465@qq.comIntroduction: Skin cutaneous melanoma is becoming more dangerous since it has a poor prognosis and is resistant to treatment. Previous research has shown that lncRNAs and fatty acid metabolism are essential for numerous biological activities. There are no studies on the relationship between fatty acid metabolism-Related lncRNAs and skin cutaneous melanoma.Methods and Results: In order to better understand the prognosis and survival of SKCM patients, we investigated the significance of lncRNAs related to fatty acid metabolism. In this work, we looked at the fatty acid metabolism genes and lncRNAs expression patterns. On the basis of lncRNAs associated with fatty acid metabolism, a nomogram and a prognosis prediction model were created. Based on the profile of lncRNAs associated with fatty acid metabolism, functional and pharmacological sensitivity investigations were also carried out. We also looked at the connection between immunotherapy and the immune response. The findings demonstrated that a risk score model based on 11 essential lncRNAs for fatty acid metabolism may discriminate between the clinical condition of SKCM and more accurately predict prognosis and survival. We conducted quantitative reverse transcription polymerase-chain reaction (RT-PCR) to verify the model.Conclusion: These important lncRNAs further showed a strong association with the tumor immune system, and these important lncRNAs also showed a connection between SKCM and chemotherapeutic treatment sensitivity. Our research strives to provide fresh viewpoints and innovative approaches to the treatment and administration of SKCM.Keywords: skin cutaneous melanoma, lncRNA, fatty acid metabolism, bioinformatics, tumor immune